Eastern borders of the Magdalenian ‘à navettes’. Maszycka cave in Lesser Poland (Southern Poland) - Kozłowski, Stefan Karol; Terberger, Thomas; Bobak, Dariusz; Orschiedt, Jörg; Połtowicz-Bobak, Marta (Société préhistorique française, 2017)
Magdalenian à navettes is the first trace of the Magdalenian presence on the territory of the eastern part of Central Europe, which is far ahead of the main phase of the Magdalenian settlement in these areas. It is represented by only one site — Maszycka Cave in Southern Poland. Particularly important is the fact that the assemblage from Maszycka Cave is quite complete. The only missing are the smallest artefacts which were not collected owing to the research methodology used in the 19th century. The entire assemblage consists of 292 lithic artefacts, 98 bone items and one pendant. Speaking of bone implements, reindeer antlers were mainly used for the production, rarely mammoth tusks and bones of horses and large ruminants. The most numerous are the different types of points (45 items), including different types of sagaies (36 items) mainly the forms with a single bevel base. As for the specific types, it is worth mentioning a series of eight navettes made from reindeer antlers, one item of bâton percé in a phallic shape and a richly carved rib. The navettes found in Maszycka Cave perfectly correspond to the forms known from the French sites, not only in terms of forms and treatment but considering their ornamentations. Stone inventory from the excavations carried out by G. Ossowski and S. K. Kozłowski consists of 292 artefacts. The recent fieldworks, conducted in 2013, have led to the identification of old debris heaps. Considering two square meters of the surface, the researchers have found more than 200 small flakes and chips, including burned items as well as shells and their fragments, small fragments of animal bones and probably human bones. Most controversial are the finds of shells, whose relation to the settlement has not yet been confirmed. The vast majority of artefacts (about 95%) is made of local Jurassic flint located near Kraków. Only about 5% of the raw material came from further distance. These raw materials come from different areas (fig. 14). Imports of stone raw materials determine the possible range of exploited territory and may also be an important indication that allows us to reconstruct migration routes. While the presence of western provenance of raw materials is easy to explain, the imports of flint from the south and especially from the east and northeast constitute an important and interesting contribution to the study discussing the range of expansion regarding the earliest groups of the Magdalenian population in Central Europe. These raw materials indicate the territories which were exploited, or at least they were within the range of interests of the Magdalenian group from Maszycka Cave. In the case of Volhynian flint, which outcrops are located in areas never occupied by Magdalenian population, we do not know whether its presence is the evidence of physical presence of a hunting group from Maszycka cave in the areas far east, or if it is a result of any relationship with the Eastern Gravettian community penetrating the areas located west from their territories. Specific finds from Maszycka Cave are human remains. Z. Kapica, the researcher who studied the bones, has identified 16 individuals, including women and children. The discussed group is not so numerous, but the presence of women and children was confirmed. Some of the bones indicated the performance of intentional human actions. A series of 14C dates obtained from animal bones, human bones and bone products allowed us to establish fairly accurate the Magdalenian settlement within a period of about 15,000 uncalibrated years BP (i.e. 19,000 – 18,000 cal BP). Thus it is possible to conclude that the materials of Maszycka Cave are not younger than the Magdalenian settlement ‘à navettes’ in France, but they fit well within the time period which was establish by the existence of facies ‘à navettes’. The episode of the settlement recorded in Maszycka Cave cannot be treated as a survival of this tradition in the East at the time when it had already disappeared in the original areas, or as a result of shifts in its later (final?) period of settlement. Date comparison also indicates that the expansion of the Magdalenian population towards east must have been relatively fast. Maszycka Cave is the only such an early, undoubtedly Magdalenian site in the eastern part of Central Europe, while lying on the eastern border of the areas occupied by Magdalenian ever (Połtowicz-Bobak, 2013). Regarding the Magdalenian settlement that took these territories on a regular basis there is approximately (over?) 1,000 years break (Bobak et al., 2013). As for the other sites belonging to Magdalenian ‘à navettes’, the Maszycka Cave is far more than 1,000 km in a straight line (fig. 16), but chronologically it fits perfectly in the period of facies functioning within the areas of France. Continuous and structured settlement as for the east areas of Central Europe by the Late Magdalenian population will take place about 1000 years later.
http://www.prehistoire.org/offres/file_inline_src/515/515_pj_290317_112800.pdf
Keywords: magdalenian; palaeolithic; Maszycka Cave; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Archaeology subjects::Archaeology